THE ETHICAL LEADERSHIP AFFECTING BUDGET MANAGEMENT IN FUNDRAISING OF SCHOOL ADMINISTRATORS UNDER THE NONGBUA LAMPHU PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Hapanna, Nantanat; Chompuwiset, Patcharin; Bubpha, Suchada (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2025)
The objectives of this research were: 1) to study the level of ethical leadership of school administrators, 2) to study the level of budget management in terms of fundraising of school administrators, 3) to investigate the relationship between ethical leadership and budget management in terms of fundraising by school administrators, 4) to construct a predictive model for the relationship between ethical leadership and budget management in terms of fundraising by school administrators, and 5) to explore strategies for developing ethical leadership that influences budget management in terms of fundraising by school administrators this research is a quantitative research that involves the collection of quantitative data from a sample consisted of 333 teachers, using stratified random sampling. the instrument was a 5-rating-scale The IOC values ranged between 0.80 – 1.00, the item discrimination ranged between 0.74 – 0.97 and the overall reliability was 0.973 and involves the collection of qualitative data from the group of informants consists of 9 experts, selected using a purposive sampling method. the research instrument is a semi-structured interview. the statistics for data analysis were frequency distribution, percentage, mean, standard deviation, Pearson’s product moment correlation coefficient and stepwise multiple regression analysis. The results of this research showed that: 1) The ethical leadership of school administrators was found to be at a high level overall. 2) The budget management for fundraising was found to be at a high level overall 3) The ethical leadership of school administrators and budget management for fundraising have a positive relationship. 4) The development of a predictive equation for ethical leadership factors affecting budget management for fundraising among school administrators identified justice (X1), respect (X4), and trust (X2) as the most significant factors influencing budget management for fundraising. These factors demonstrated a statistically significant impact at the 0.01 level. The multiple correlation coefficient (R) was 0.631, and the coefficient of determination (R2) was 0.398, indicating a predictive power of 39.80%. 5) The approaches for developing ethical leadership that influence budget management in fundraising were found to comprise a total of eight approaches.